The Spectacle of History / Speech, Text, and Memory at the Iran-Contra Hearings - Bogen David; Lynch Michael (Duke University Press, 1996)
A unique insight into problems at the heart of society and social theory. Preface, Transcription Conventions, Introduction, The Sincere Liar, The Production of History, The Ceremonial of Truth, The Truth-Finding Engine, Stories and Master Narratives, Memory in Testimony, The Documentary Method of Interrogation, Conclusion: A Civil Lesson in the Logic of Sleaze, Methodological Appendix: Post Analytic Ethnomethodology, Notes, Index.